TOWARDS BUMDES 4.0: E-COMMERCE-BASED MSME PRODUCT MARKETING ASSISTANCE TRAINING AT BUMDES BALAI BATU SANDARAN VILLAGE, BARANGIN DISTRICT, SAWAHLUNTO CITY - Nurofik, Agus; Amran, Ali; Tio, Lina; Permana, Hendrik; Hendri, Novi (TOPLAMA, 2025)
This service program aims to provide product marketing assistance through an E-Commerce-based digital platform for BUMDesa Balai Batu Sandaran, Barangin District, Sawahlunto City. It is expected that this program can serve as a solution for product marketing by fostering a digital ecosystem for BUMDesa management. Additionally, BUMDesa digitization supports the achievement of the Sustainable Development Goals (SDGs), particularly point nine, which focuses on infrastructure, industry, and innovation. The implementation of this program consists of three main stages: socialization, program implementation, and monitoring and evaluation. The first stage involves socializing the program to all BUMDesa administrators and informing them of its objectives and benefits. The second stage focuses on implementation, including assistance in creating E-Commerce accounts and digital marketing training for BUMDesa products. Finally, the monitoring and evaluation phase assesses the program’s effectiveness, its impact on the community, and the alignment between planning and execution. The advancement of information technology has brought significant transformations across various sectors, including the local economy. This study explores the implementation of Bumdes 4.0 through E-Commerce-based MSME product marketing assistance training at BUMDesa Balai Batu Sandaran. The training is designed to enhance MSME actors’ ability to market their products online, leveraging E-Commerce platforms to reach a broader market. Through a participatory and collaborative approach, this training not only provides technical skills but also effective marketing strategies.